Las asimetrías de la enfermedad holandesa. Revisando el modelo petrolero noruego, 1970-2018 - Eszter Wirth; Juan M. Ramírez-Cendrero (Revista Iberoamericana de Estudios de Desarrollo)
In this article, it is traced the presence of the Dutch disease (DD) in the Norwegian economy, which entails the analysis of both its manifestations and links to policies. After systematizing the oil industry’s configuration throughout the period 1970-2018, the impact of the oil sector on the rest of the economy is outlined in conjunction with the Norway’s dependency on the former industry. Specifically, no clear resource reallocation effects of the DD can be observed, although there are certain traces of its spending effects. Moreover, despite the relatively low oil dependency ratios in comparison with other oil producers, the whole of the Norwegian economy shows strong linkages to the oil sector and the trade balance has suffered from increasing deficits related to manufactured products with higher technology content. Based on these results, the faint manifestations of the DD in Norway are diagnosed, which enables us to offer contributions in terms of development policies for oil-rich countries.